Shortened Taper Duration after Implementation of a Standardized Protocol for Iatrogenic Benzodiazepine and Opioid Withdrawal in Pediatric Patients: Results of a Cohort Study - Vipond, Jane M. (Pediatr Qual Saf, 2018)
INTRODUCTION: Methadone and lorazepam prescribing discrepancies for the use of iatrogenic withdrawal were observed among providers. A standardized pharmacist-managed methadone and lorazepam taper protocol was implemented at a pediatric tertiary care facility with the aim to reduce the length of taper for patients with iatrogenic withdrawal. METHODS: A multidisciplinary team of nurses, pharmacists, and physicians reviewed the current literature, then developed and implemented a standardized withdrawal taper protocol. Outcomes were compared with a retrospective control group using past prescribing practices. The primary endpoint was the length of methadone and/or lorazepam taper. Secondary endpoints included evaluation for significant differences between the control and standardized protocol groups regarding additional breakthrough withdrawal medications, pediatric intensive care unit (PICU) and hospital length of stay. We also evaluated provider satisfaction with the protocol. RESULTS: The standardized protocol group included 25 patients who received methadone and/or lorazepam taper. A retrospective control group contained 24 patients. Median methadone taper length before protocol implementation was 9.5 days with an interquartile range (IQR) of 5.5–14.5 days; after protocol implementation, it was 6.0 (IQR, 3.0–9.0) days (P = 0.0145). Median lorazepam taper length before protocol implementation was 13.0 (IQR, 8.0–18.0) days; after protocol implementation, it was 6.0 (4.0–7.0) days (P = 0.0006). A statistical difference between PICU length of stay, hospital length of stay, or the number of additional medications for breakthrough withdrawal was not found. CONCLUSIONS: The use of a standardized withdrawal protocol resulted in shorter taper duration for both the methadone and lorazepam groups. There was no difference in PICU or hospital length of stay.